Analisis Hukum Islam Terhadap Ketentuan Nafkah Mut'ah Pada Perkara Cerai Gugat Dalam Hukum Positif Di Indonesia - Wawan Irwansyah; Nia Maulina; Wiranti Wiranti; Rahmat Hidayat; Irwan Irwan (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2025)
This study addresses the legal norm disparity concerning the provision of nafaqah mut’ah (consolation maintenance) in wife-initiated divorces. While Islamic law and Indonesia’s Compilation of Islamic Law generally grant such maintenance to wives divorced by their husbands, the regulation is unclear when the wife files for divorce. This research aims to examine the legal standing of nafaqah mut’ah for wives initiating divorce, within the framework of Islamic and Indonesian positive law. A qualitative descriptive-analytical method was applied, involving document analysis and interviews with judges and legal practitioners. The findings show that nafaqah mut’ah is typically not granted in such cases unless the court determines that the husband bears fault in the marital breakdown. These findings underscore the need for legal reform in Islamic family law to enhance gender justice and legal certainty, aligning with the broader objectives of Islamic law in promoting fairness and public welfare.